2007
DOI: 10.1063/1.2732680
|View full text |Cite
|
Sign up to set email alerts
|

Interface roughening and defect nucleation during solid phase epitaxy regrowth of doped and intrinsic Si0.83Ge0.17 alloys

Abstract: Metastable pseudomorphic Si 0.83 Ge 0.17 with thickness of 135 nm was deposited on ͑001͒ Si substrate by molecular beam epitaxy and amorphized to a depth of ϳ360 nm, using 3 ϫ 10 15 cm −2 Ge ions at 270 keV. Samples were regrown by solid phase epitaxy in the 500-600°C temperature range. The regrowth rate was measured in situ by time resolved reflectivity, while the structure of the epilayers was investigated by transmission electron microscopy. Three regions can be distinguished in SiGe after solid phase epita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Obtaining high quality and smooth crystalline SiGe, especially with high Ge content, directly on silicon is therefore challenging. SPE of amorphous SiGe layers produced by ion implantation has previously been studied in detail where it was shown that the SPE activation energy generally decreases with Ge content and that the amorphous-crystalline interface can become rough as a result of the strain [10,11]. Graded SiGe layers is a common method employed to control the formation of dislocations but such a process may require additional processing steps [12].…”
Section: Introductionmentioning
confidence: 98%
“…Obtaining high quality and smooth crystalline SiGe, especially with high Ge content, directly on silicon is therefore challenging. SPE of amorphous SiGe layers produced by ion implantation has previously been studied in detail where it was shown that the SPE activation energy generally decreases with Ge content and that the amorphous-crystalline interface can become rough as a result of the strain [10,11]. Graded SiGe layers is a common method employed to control the formation of dislocations but such a process may require additional processing steps [12].…”
Section: Introductionmentioning
confidence: 98%